WORKER SAFETY DURING EXCAVATION AND TRENCHING CONSTRUCTION WORK - Radosavljević, Jasmina; Vukadinović, Ana; Đorđević, Amelija (Facta Universitatis, Series: Working and Living Environmental Protection, 2021)
Earthworks are the integral part of any construction work in civil engineering and building construction. The construction activities performed during earthworks include the following: excavation, earthmoving, earth transport, and earth compaction. During earthworks, the excavation site is subject to harmful, flammable, or hazardous materials, damage to underground installations, the collapse of the earth, and many more risks. Therefore, construction work for trenching and excavation requires the implementation of adequate safety measures. This paper discusses the safety measures for workers during earthworks that involve excavations up to and exceeding one meter in depth.